Evaluating the Need for Creativity and Metacognition in STEM Integration for Sustainable Education within the Pancasila Student Profile Strengthening Project - Anisa Puteri; Didit Ardianto; Indarini Dwi Pursitasari (Journal of Science Education Research, 2026)
This study explores the integration of metacognitive strategies, STEM elements, creativity, and Assessment as Learning (AaL) within the Pancasila Student Profile Project (P5) teaching materials in Indonesia’s Kurikulum Merdeka. Utilizing a qualitative design, the research involved rubric-based analysis of 32 P5 modules and semi-structured interviews with 10 teachers from urban and rural schools. Findings revealed that while the modules address themes of sustainability, they remain narrowly focused and exhibit moderate integration of ESD (1.3), creativity (0.5), STEM (1.6), and metacognitive scaffolding (1.3). The materials often lacked open-ended problem-solving, project-based design, and reflective prompts essential for fostering creativity and self-regulated learning. Triangulated data showed consistency between module analysis and teacher perspectives, highlighting gaps in problem-action alignment and superficial STEM applications. Thematic analysis also identified limited teacher familiarity with AaL and STEM-PjBL, reinforcing the need for targeted professional development. The study concludes that strengthening teacher capacity, scaffolding inquiry-based strategies, and revising assessment frameworks are critical to enhancing the transformational potential of P5 for 21st-century learning.